Virulence gene mutations as a differentiator of clinical phenotypes: insights from community-acquired uropathogenic Escherichia coli. Issue 4 (5th April 2022) - Yadav, Manisha; Pundir, Swati; Kumari, Rajesh; Kumar, Arvind; Venugopal, Shwetha J.; Panigrahy, Rajashree; Tak, Vibhor; Chunchanur, Sneha K.; Gautam, Hitender; Kapil, Arti; Das, Bimal; Sood, Seema; et al.
Abstract : Uropathogenic Escherichia coli (UPEC) remains an important cause of urinary tract infection during pregnancy. Multiple molecular virulence determinants and antibiotic resistant genes facilitate its pathogenesis and virulence phenotype. Hence it is hypothesized that there will be considerable variation in genes among the isolates from symptomatic as well as asymptomatic bacteriuria (ABU) during pregnancy. The aim of this study was to decipher the genetic variation among the two phenotypes. Six different UPEC isolates collected from urine specimens of consecutive pregnant females (five, symptomatic bacteriuria and one, ABU) were tested for their growth kinetics, and biofilm formation. A total of 87 virulence determinants and 56 antibiotic resistance genes were investigated using whole-genome sequencing, to identify putative drives of virulence phenotype. In this analysis, we identified eight different types of fully functional toxin antitoxin (TA) systems [HipAB, YefM-YoeB, YeeU-YeeV (CbtA), YhaV-PrlF, ChpBS, HigAB, YgiUT and HicAB] in the isolates from symptomatic bacteriuria; whereas partially functional TA system with mutations were observed in the asymptomatic one. Isolates of both the groups showed equivalent growth characteristics and biofilm-formation ability. Genes for an iron transport system (Efe UOB system, Fhu system except FhuA) were observed functional among all symptomatic and asymptomatic isolates, however functional mutations were observed in the latter group. Gene YidE was observed predominantly associated with the biofilm formation along with few other genes (BssR, BssS, YjgK, etc.). This study outlines putative critical relevance of specific variations in the genes for the TA system, biofilm formation, cell adhesion and colonization among UPEC isolates from symptomatic and asymptomatic bacteriuria among pregnant women. Further functional genomic study in the same cohort is warranted to establish the pathogenic role of these genes.